Vasoactive Intestinal Peptide Receptor, CRTH2, Antagonist Treatment Improves Eosinophil and Mast Cell-Mediated Esophageal Remodeling and Motility Dysfunction in Eosinophilic Esophagitis - Chandra Sekhar Yadavalli; Sathisha Upparahalli Venkateshaiah; Alok K. Verma; Chandrasekhar Kathera; Pearce S. Duncan; Michael Vaezi; Richard J. Paul; Anil Mishra (Cells, 2024)
Background and Aims: Ultrasonography has shown that eosinophils accumulate in each segment of the esophageal mucosa in human EoE, ultimately promoting esophageal motility dysfunction; however, no mechanistic evidence explains how or why this accumulation occurs. Methods: Quantitative PCR, ELISA, flow cytometry, immunostaining, and immunofluorescence analyses were performed using antibodies specific to the related antigens and receptors. Results: In deep esophageal biopsies of EoE patients, eosinophils and mast cells accumulate adjacent to nerve cell-derived VIP in each esophageal segment. qRT-PCR analysis revealed five- to sixfold increases in expression levels of VIP, CRTH2, and VAPC2 receptors and proteins in human blood- and tissue-accumulated eosinophils and mast cells. We also observed a significant correlation between mRNA CRTH2 levels and eosinophil- and nerve cell-derived VIPs in human EoE (p < 0.05). We provide evidence that eosinophil and mast cell deficiency following CRTH2 antagonist treatment improves motility dysfunction in a chronic DOX-inducible CC10-IL-13 murine model of experimental EoE. Conclusions: CRTH2 antagonist treatment is a novel therapeutic strategy for inflammatory cell-induced esophageal motility dysfunction in IL-13-induced chronic experimental EoE.